El uso de alcohol en la adolescencia como un ritual de transición, desde el enfoque sistémico, aplicado a estudiantes de sexto curso de un colegio de la ciudad de Quito. - Acosta, Julio (2010)
This research stems from seeking a nuclear point of reflection of alcohol in our culture, adolescence stands out as the period of life in which this behavior materializes, generating lessons that develop individual lifestyles, family, community likely the rest of the life cycles will continue. It highlights the main characteristics of adolescence that can influence the learning process physiological, cognitive, psychological, moral level, this in relation to the main stages and tasks of adolescence, it recognizes the existence of a large majority of teenagers no major surprises, and a rather small percentage who have difficulties, this reflects that are standardized behaviors that do not call attention to be expected, one of them is the use of alcohol, as a sign of leaving childhood and start a transition to adulthood by adopting certain behaviors of culture.